Housing maintenance in multi-habited low-income houses in Accra. - Addo, A.I (Nova Science Publishers, Inc., 2016)
Globally, the rising maintenance cost in buildings poses a great deal of challenge for homeowners. The UN Habitat Global Housing Strategy framework identifies housing maintenance as one of the thematic areas that require special attention and improvement if the building life will be sustained. In Ghana, maintenance of buildings is often neglected in housing development and research shows that a large proportion of residential buildings in public institutions have maintenance problems. Although these buildings are publicly owned and maintained, they still have challenges maintaining them. The challenge becomes heightened when the buildings are privately maintained by low income households. The paper sought to interrogate how maintenance occurs in multi-habited low income houses in some urban low income communities in Accra. Both quantitative and qualitative research approaches were employed in the primary data collection. The results show that multi-habited low income houses in Accra are poorly maintained and this problem is pronounced in the family houses in the indigenous communities like James Town and Tema Manhean. House owners often adopt the reactive maintenance approach, while waiting for the building component to completely spoil before replacing. Housing maintenance is strongly correlated with the incomes of the households. It is recommended that households should have access to maintenance loans and this will greatly improve the physical condition of multi-habited low income houses in Accra.
Keywords: housing; maintenance; urban; low income; multi-habited; Accra